Thalassemia PBL Case - Niels Larsen; Diana Callender; Kalman Winston (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a problem-based learning (PBL) case on alpha-thalassaemia syndrome (i.e., patient with Hemoglobin H disease). At our university, medical genetics is taught in first and second semester, so this version of the case most naturally is directed at first-year medical students in a similar program. However, the case can easily be altered to involve more pathology for use in medical schools that teach genetics during the second year. Methods The case naturally leads the students to study causes of fatigue and then anemia, especially microcytic anemia. Students then compare and contrast thalassaemia with iron deficiency anemia. This PBL case involves three sessions. Students are presented with the first five pages of the case in session one. After students learn and discuss the research in session two, the students are presented with additional notes. Finally during session three the postscript and expected learning issues are handed out. As our expectation is that no facilitator can be an expert in all aspects of a case, a Faculty Notes file with background information is included. Results This case was developed during 2005 and has since been used in the author's PBL program once to twice a year. It has proven to be a well-functioning case which generally has been well received by facilitators and students alike. Discussion The case requires the students to interpret a hemoglobin electrophoresis pattern presented as an illustration. An expected learning issue involves the review of population incidence differences in the occurrence of hemoglobinopathies. Appropriate genetic counseling is most often also researched.